Faktor risiko servisitis pada wanita pekerja seks di kegiatan layanan infeksi menular seksual mobile - Mayta Sari Dwianggimawati; Sunardi Radiono; Theodola Baning Rahayujati (Berita Kedokteran Masyarakat (BKM), 2017)
Risk factors of cervicitis among female sex workers in sexual transmitted infection mobile servicePurposeThis study aimed to identify risk factors of cervicitis among female sex workers in the district of Cilacap. MethodsThis study used a cross-sectional design. Total of respondents were 147 female sex workers who participated in the mobile sexual transmitted infection services. Demographic characteristic and risk factor data were collected by interviews using a structured questionnaire. Diagnosis of cervicitis was obtained by laboratory test with cervix swab. Data were analyzed using Poisson regression test with robust variance estimators.ResultsPrevalence of cervicitis among female sex workers in the district of Cilacap were 70.75%. Multivariate analysis showed that the risk factors of cervicitis among female sex worker were: age ≤24 years old, income, childbirth history, number of clients per week, and inconsistent of condoms use.ConclusionsResults showed the need to increase awareness of condom use among female sex workers through health promotion and counseling in mobile sexual transmitted infection services by the teams of sexual transmitted infection clinics. Potential targets for outreach health promotions and counseling are younger female sex worker (≤30 years old).